Levels of some heavy metals in autistic patients in Nasiriya City, Southern Iraq. - Afaq T. Farhood (University of Thi-Qar Journal, 2019)
The aim was to assess the blood levels of heavy metals (Copper – Zinc and lead) in autistic patients where have these metals could be correlated with this disease. This study was conducted on 498 autistic patients aged between 1-16 years of both sexes , at the autism center in Thi-qar health department official center during 2016 . Blood samples were collected from patients analyzed for Pb , Cu , Zn . The results showed increase in the levels of (Cu- Zn and Pb) : Pb> Cu>Zn . The result also, showed that there is a relationship between the disease and the age, where the age group (4-6 years) recorded the highest percentage, as well as the relationship of a positive correlation with (A blood group) as follows A > B> AB > O , the sex percentage was recorded that (9 :1) males :females . The conclusion of this high percentage of male to female might be due to sex–affected or from environmental impacts which are have more influence on males .